Nursing perception and work effectiveness evaluation relating to a novel nursing role in the Italian scenario: the family nurse: The Italian family nurse - Vitale, Elsa (Medicina Historica, 2023)
The present study aims to understand the Italian nurses’ perceptions on this new figure-role, specifically to understand the effectiveness level nurses attribute to this novel professional figure. Furthermore, perceptions are differentiated according to some socio-demographic variables considered in the interviewed nurses, as: gender, age, years of work experience and nursing education level. The questionnaire was administered online and was made up of two sections: the first section referred to some socio-demographic characteristics and the second part included the Work Effectiveness questionnaire, which contained a total of 19 items divided into 6 sub dimensions, as: access to opportunity, to information, to support, to resources, to informal and formal power. The results obtained showed a mild level in perception on work effectiveness in all the six sub dimensions considered, as: access to opportunity, access to information, access to support, access to resources, access to informal and formal power, respectively. By considering all the work effectiveness sub dimensions differentiating by socio-demographic variables, it was highlighted that nurses who reported higher educational level in nursing registered also higher perception in family nursing role in the access to opportunity (p=.001), to information (p=.001), to support (p=.024) and to resources (p=.002), respectively. While no socio-demographic variable was considered determinant in the access to formal power sub dimension and as regards the access to informal power females reported significantly higher levels than males (p=.025), respectively. Nurses referred their clinical positive results to the intensive educational chances to acquire and implement knowledge which were established to improve nursing development for family nurses by being in a role that kept professional development and success.